PENINGKATAN PRODUKTIVITAS TANAMAN MENTIMUN BABY (Cucumis sativus L. ) ORGANIK DENGAN PEMBERIAN DOSIS PUPUK KOTORAN KELELAWAR - Diah Sri Utami; Mariyatul Qibtiyah; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Cucumber is one of the vines that is usually eaten directly or in processed form. The productivity of this cucumber crop is quite low. Cucumber production can be increased through intensification efforts. Intensification is a step taken to increase agricultural productivity through optimal utilisation of available land with various methods. One of them is the use of bat manure (Guano) fertiliser. Guano fertiliser comes from the process of weathering rocks and bat droppings that occur in natural caves containing nutrients N, P, and K. This research is to determine how effective the dose of Guano fertiliser is in increasing the productivity of organic cucumber. The research used the regular Randomised Group Design (RAK) method involving 7 treatments and 4 replications. The parameters observed were the dose of guano fertiliser, from no guano fertiliser; 2.5 t/ha; 5.0 t/ha; 7.5 t/ha; 10.0 t/ha; 12.5 t/ha; and 15.0 t/ha. Parameters that have been observed include number of leaves, plant height, fruit weight per hectare, fruit weight per plot, and fruit weight per sample plant. The data obtained will be calculated with the F test at 1 and 5% significance levels. If there is a significant difference, the next step is the BNT test at the 5% significance level. The optimal result of bat manure fertiliser dosage on baby cucumber productivity was found when using the highest dose, 15.0 t/ha, compared to other doses.